Clinical Use of the Kannada and English Rate of Reading Tests - Srinivasan, Krithica; Gilchrist, James M.; Krishnan, Gopee; Wilkins, Arnold; Allen, Peter M. (Frontiers in Psychology, 2019)
The Rate of Reading Test in which randomly ordered common words are read aloud has found use in optometric and educational practice as a means of assessing visual aspects of reading largely independently of comprehension. English and Kannada versions of the Rate of Reading Test were administered on 761 children aged between 9 to 15 years. These children were recruited from four private and five state schools in Udupi Taluk that had English and Kannada, respectively, as the principal medium of instruction. The results showed that the reading rate increased with age, as expected, but depended on the language of the test and the medium of instruction. The study emphasizes the importance of using normative data based on age and the language used in school. It also suggests age-specific criteria to measure the efficacy of any visual intervention aimed at improving reading speed. The test can be used to assess (1) educational under-performance in reading and (2) the effects of optometric and educational intervention, and separate norms appropriate for each use are presented.